Recovery of visual field defects following vitrectomy for proliferative diabetic retinopathy: A case report. Issue 48 (3rd December 2021) - Lo, Kang-Jung; Yang, Jin-Han; Cheng, Hui-Chen; Chang, Hsin-Yi; Lin, Tai-Chi
Abstract: Rationale: Proliferative diabetic retinopathy (PDR) may lead to severe visual impairment, and visual field (VF) loss in such patients has been reported. Vitrectomy is performed in PDR cases complicated with either vitreous hemorrhage or tractional retinal detachment to restore their visual acuity. However, its effect on VF defects is limited in data. Herein, we report the recovery of VF defects following vitrectomy in a patient with PDR. Patient concerns: A 25-year-old female with bilateral PDR and vitreous hemorrhage received 2 monthly intravitreal injections of aflibercept in both eyes. Six months after her last injection, she presented with fibrovascular membrane formation in both eyes and VF defects of −9.02 dB and −20.05 dB in the right and left eye, respectively. Diagnoses: Proliferative diabetic retinopathy in both eyes. Interventions: The patient underwent vitrectomy for her left eye. Outcomes: Although her visual acuity did not improve as expected, results from the Humphrey visual field analyzer showed notably improvement of her left eye (−9.05 dB) after the surgery. Lessons: Vitrectomy potentially allows recovery of VF defects in patients with PDR.